Graha Block, Inovasi Block Rumah Adat Berbasis Permainan Interaktif Untuk Melestarikan Kebudayaan Tradisional Indonesia - Fandika Agustiyar; Dewi Rizqiyana; Aldi Riyanto; Nur Hidayah; Sabda Alam; Rema Bagos Pudyastowo; Suherman Suherman (STKIP PGRI SITUBONDO, 2023)
The architecture of traditional Indonesian houses is a very important cultural heritage of this nation. Traditional houses not only function as a place to live, but also as a representation of cultural values that describe people's behavior. However, now traditional house architecture is starting to be marginalized by many modern house designs or concepts, so creative efforts are needed to re-popularize traditional Indonesian house architecture. Grha Block is a block-based toy made in the form of traditional Indonesian house architecture with the aim of popularizing the shape of Indonesian traditional houses. The steps taken to run a business, namely: business planning, production, marketing and business development. Grha Block carries three types of architecture, namely Rumah Gadang (West Sumatra), Rumah Joglo (Central Java) and Rumah Tongkonan (South Sulawesi) and is equipped with information about the culture and traditional houses concerned which can be accessed via barcodes on product packaging. Grha Block has sold 9 units in 21 days with a turnover of Rp3.148.000,00 while the break-even point is 17 units in 81 days with a turnover of Rp6.770.000.00 Grha Block can be a means of cultural education for the community through its unique and attractive form, which has business value and deserves to be developed..